2018
DOI: 10.1039/c8tc00329g
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced insulating and piezoelectric properties of 0.7BiFeO3–0.3BaTiO3lead-free ceramics by optimizing calcination temperature: analysis of Bi3+volatilization and phase structures

Abstract: The significantly enhanced insulating and piezoelectric properties are obtained in 0.7BiFeO3–0.3BaTiO3 ceramic by fine-tuning the calcination temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(34 citation statements)
references
References 50 publications
0
34
0
Order By: Relevance
“…As a new environment-friendly lead-free piezoelectric system, the BiFeO 3 –BaTiO 3 (BF-BT) solid solution has been paid attention since water-quenched BF-BT ceramics with BiGaO 3 doping have been reported to have high performance together with a high phase transition Curie temperature ( T C ) . Recently, unmodified and modified BF-BT ceramics prepared by using air- and/or water-quenching processes showed enhanced ferroelectric and piezoelectric properties. Zheng and Wu reported that the enhanced ferroelectric and piezoelectric properties in BF-BT ceramics by optimizing water-quenching process, calcination, and sintering conditions, but its direct piezoelectric sensor coefficient, d 33 , was ∼170 pC/N . The best d 33 values reported in water-quenched, air-quenched, and furnace-cooled ceramics were 200, 191, and 210 pC/N with T C of 500, 530, and 507 °C, respectively, in previous literature. There is no significant difference in d 33 between air/water-quenched and furnace-cooled ceramics because the unstable BF was not considered in heat-treatment conditions such as calcination, sintering, binder burning, and external-electrode firing temperature.…”
Section: Introductionmentioning
confidence: 99%
“…As a new environment-friendly lead-free piezoelectric system, the BiFeO 3 –BaTiO 3 (BF-BT) solid solution has been paid attention since water-quenched BF-BT ceramics with BiGaO 3 doping have been reported to have high performance together with a high phase transition Curie temperature ( T C ) . Recently, unmodified and modified BF-BT ceramics prepared by using air- and/or water-quenching processes showed enhanced ferroelectric and piezoelectric properties. Zheng and Wu reported that the enhanced ferroelectric and piezoelectric properties in BF-BT ceramics by optimizing water-quenching process, calcination, and sintering conditions, but its direct piezoelectric sensor coefficient, d 33 , was ∼170 pC/N . The best d 33 values reported in water-quenched, air-quenched, and furnace-cooled ceramics were 200, 191, and 210 pC/N with T C of 500, 530, and 507 °C, respectively, in previous literature. There is no significant difference in d 33 between air/water-quenched and furnace-cooled ceramics because the unstable BF was not considered in heat-treatment conditions such as calcination, sintering, binder burning, and external-electrode firing temperature.…”
Section: Introductionmentioning
confidence: 99%
“…According to the author's current knowledge, the ultrahigh temperature stability of the piezoelectric response, as well as high Curie temperature, has rarely been reported in lead‐free ceramics by traditional ceramic technology without any thermal treatment, indicating that the BFM‐BT ceramics may be candidates for high temperature piezoelectric ceramics (Table 4). 33‐41 …”
Section: Resultsmentioning
confidence: 99%
“…In the previous literature, it is known that the deviation from oxygen stoichiometry leads to valence fluctuation of Fe ions (+3 to +2 state) in BFO [ 31 ]. Pure BFO shows poor properties due to due to the oxygen vacancies derived from the reduction of Fe 3+ to Fe 2+ and Bi 3+ volatilization [ 32 ]. For the sake of determining the elements, elemental oxidation states, chemical shifts and oxygen vacancies in doped BFO thin film, detailed XPS measurements are also carried out.…”
Section: Resultsmentioning
confidence: 99%